Assessment of musculoskeletal disorders among nurses at private hospitals / Vanitha Chantiran - Vanitha, Chanthiran (2022)
Ergonomics is the study of making workplaces and work, tasks more compatible with the physical and mental capabilities of the people there. The goal of ergonomics is to decrease stress and prevent injuries and illnesses caused by muscle fatigue, poor posture, and repetitive job tasks. This research aims to assess the prevalence of musculoskeletal disorders (MSDs) among nurses at private hospitals. A descriptive cross-sectional design utilized for carrying out this study. The study addressed nurses within selected private hospitals (N=169). The tool used to collect data was a set of questionnaires including persistent of job risk factors, factors that affect the level of awareness and Nordic Musculoskeletal Questionnaire (NMQ). According to the study's findings, nurses are increasingly vulnerable to MSDs. Furthermore, there was a highly statistically significant positive link (p-value 0.05) between employment risk factors, factors influencing MSD awareness, and prevalence of MSDs among nurses working in private hospitals. The study recommended that the hospitals’ organization as they devise strategies for reducing MSDs health risks in the workplace. It is important to make sure that the workplace (hospital) has an ergonomic work environment, educate, and communicate the risk factors of MSDs as well as to provide workshop on application of ergonomic principles at workplace. Combining interventions aimed at the organization and the individual to combat MSDs in the healthcare industry. Though the nurse should embed physical exercise in their daily tasks. Physical exercise is strong therapeutic modality to reduce musculoskeletal pain or discomfort and enhance the quality of life. Besides that, the nurses also should show their commitment towards the organization’s every endeavor and attempt on reducing MSDs. Nurses should strongly prepare themselves room for improvements. MSDs in the healthcare industry may be prevented or minimized with clear policies, strategies, and safety culture based on the management support, nurses’ involvement, and rigorous change procedures. MSDs on the rise, and more study is needed to find ways to minimize their frequency, incidence, and long-term impact. Also, the future studies should be performed to investigate the relationship between MSDs and other variables such as demographic background, job performance and job satisfaction.